ISUP Consensus Definition of Cribriform Pattern Prostate Cancer. (August 2021) - van der Kwast, Theodorus H.; van Leenders, Geert J.; Berney, Daniel M.; Delahunt, Brett; Evans, Andrew J.; Iczkowski, Kenneth A.; McKenney, Jesse K.; Ro, Jae Y.; Samaratunga, Hemamali; Srigley, John R.; Tsuzuki, Toyo; Varma, Murali; et al.
Abstract : The presence of a cribriform pattern is now recognized as a clinically important, independent adverse prognostic indicator for prostate cancer. For this reason the International Society of Urological Pathology (ISUP) recently recommended its inclusion in standard reporting. In order to improve interobserver agreement as to the diagnosis of cribriform patterns, the ISUP assembled an international panel of 12 expert urogenital pathologists for the purpose of drafting a consensus definition of cribriform pattern in prostate cancer, and provide their opinions on a set of 32 images and on potential diagnostic criteria. These images were selected by the 2 nonvoting convenors of the study and included the main categories where disagreement was anticipated. The Delphi method was applied to promote consensus among the 12 panelists in their review of the images during 2 initial rounds of the study. Following a virtual meeting, convened to discuss selected images and diagnostic criteria, the following definition for cribriform pattern in prostate cancer was approved: "A confluent sheet of contiguous malignant epithelial cells with multiple glandular lumina that are easily visible at low power (objective magnification ×10). There should be no intervening stroma or mucin separating individual or fused glandular structures" together with a set of explanatory notes. We believe this consensus definition to be practical and that it will facilitate reproducible recognition and reporting of this clinically important pattern commonly seen in prostate cancer. The images and the results of the final Delphi round are available at the ISUP website as an educational slide set (https://isupweb.org/isup/blog/slideshow/cribriform-slide-deck/ ). Abstract : Supplemental Digital Content is available in the text.